A review of the management and outcome of patients admitted with cryptococcal meningitis at a regional hospital in KwaZulu-Natal province - Andrew J. Ross; Egide Ndayishimiye (South African Family Practice)
Background: South Africa has 7.06 million people who are HIV-positive, with those having a low CD4 count being susceptible to cryptococcal meningitis (CCM), which has an estimated mortality of 30–50%. This study aimed to establish the outcome of patients admitted with CCM to a regional hospital in Durban between June 2015 and May 2016, and the extent to which the National Department of Health (NDoH) protocol was adhered to in managing their condition. Method: This retrospective observational descriptive study reviewed the records of patients ≥ 12 years old admitted with CCM between June 2015 and May 2016, from which their demographic and medical data were extracted. Results: Seventy-six complete records were found of which 49 were men and 27 were women. The average CD4 count was 55.9 cells/mm3, 85.5% were treated with intravenous amphotericin B and high-dose oral fluconazole, 6.7% received only amphotericin B and 5.2% received only fluconazole. There was an in-hospital mortality of 31.6%, and the NDoH protocol was adhered to in 72.4% (55/76) of patients. There was, however, no significant difference in outcome between those who were and were not managed as per the protocol (p = 0.177). Discussion and conclusion: In-hospital mortality for CCM continues to be significant despite high rates of adherence to the NDoH protocol in the majority of patients. For this to be addressed, early diagnosis of HIV and initiation of ART to prevent the profound immunosuppression is essential.